THE EFFECT OF GOAT FERTILIZER DOSAGE ON RESULTS CUCUMBER VARIETY (Cucumis sativus L.) - Tegar Dadang Pradigma; Priyono; Saiful Bahri (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
Effect of the dose of goatmanure on the yield of cucumber varieties (Cucumis sativus L.). This researchwas conducted in the experimental garden of the Faculty of Agriculture, Slamet Riyadi University,Surakarta, Central Java, on December 20, 2021 - February 25, 2022. The purpose of this study was todetermine the effect of goat manure on cucumber varieties. The experimental design used a completelyrandomized design (CRD) was arranged with a split plot design, with 3 types of varieties (V) Metavy,Ethana, and Mercy with doses of goat manure (K) 300 gr, 400 gr, and 500 gr. The dose of goat manureat a dose of 500 g/plant on the Metavy variety showed the best average results on the observation offruit length, fruit weight, fruit diameter, while the number of fruit had no effect. The dose of goat manure500 gr/plant on the Ethana variety showed the best average results in observing fruit length, fruit weight,fruit diameter, while the number of fruit had no effect. Dosage of goat manure at a dose of 500 g/planton the Mercy variety showed the best average results on observations of fruit length, fruit weight, fruitdiameter, while the number of fruit had no effect.Keyword : Cucumber; Variety; Goatmanure.